Work-place cancer and palliative care interprofessional education: experiences of students and staff. Issue 1 (2nd January 2023) - McKinlay, Eileen; White, Kristen; Garrett, Sue; Gladman, Tehmina; Pullon, Sue
ABSTRACT: Workplace-based interprofessional education (IPE) offers opportunities for pre-registration students to interact with patients in authentic settings. Senior dietetic, medical, nursing, physiotherapy and radiation therapy students took part in a workplace IPE initiative on cancer and palliative care informed by experiential learning theory and run by clinical tutors. Research was undertaken to gauge students and tutors' experiences of the initiative. The mixed methods approach included: Pre and post-administration of the University of West England Interprofessional questionnaire 'Communication and Teamwork Scale, 'Interprofessional Learning Scale, ' 'Interprofessional Interaction Scale.' Two questions were added relating to cancer and palliative care. Separate focus group interviews were held with students and tutors. There was a positive shift in the Communication and Teamwork scale based on students' pre and post questionnaires, but no change in the other two scales. Analysis of student and tutor focus group data showed that both affirmed the IPE initiative for a range of reasons. A brief experiential, theory-informed IPE initiative with a focus on cancer and palliative care was well received by both students and clinical tutors. The mixed method approach highlighted some discrepancies between quantitative and qualitative results but when synthesized were explicable, demonstrating the value of using a mixed methods approach to research.